Patrakomala as Bandung City Government Innovation in Reorganizing the Creative Economy Post-Covid-19 Pandemic - Diki Suherman; Siti Aliya; Andre Ariesmansyah; Dzarin Gifarian Khaulani (Department of Public Administration, 2022)
The city of Bandung is one of the centers of the tourism sector, especially in the creative economy in Indonesia, which has experienced a decline in the number of tourists or visitors during the outbreak of the Covid-19 pandemic. This study aims to find out and analyze the innovations the Bandung city government has reorganized the Creative Economy Post-Covid-19. The method used in this research is literature review. In addition, data analysis techniques use content analysis. Collaborative Governance is the theory used in this paper. The results of this study are innovations carried out by the Bandung city government to reorganize the creative economy, especially Post-Covid-19, namely by launching and simultaneously launching the Patrakomala digital web portal (Sustainable Creative Economy Application Patron), which features digital information services for tourists. to help detect tourist destination points that become destinations, such as culinary, craft, fashion, game applications, and so on. The existence of Patrakomala is a policy innovation for the Regional Government of the City of Bandung so that it can develop the creative economy of the City of Bandung as a whole which will have implications for improving people's welfare through local economic growth. Patrakomala is also expected to become a medium of information and communication, as well as a place for creative economy education in the city of Bandung.